How Developing and Implementation Microlearning in Educational Setting?: A Literature Review - Putri, Lara Febri Dwi; Mustaji, Mustaji; Sumarno, Alim (UNDIKMA, 2024)
The use of microlearning can help students to focus more on the learning process. Thus, this article aims to analyze various studies related to microlearning in educational institution from 2019 to 2023. The method used in this research is literature review. The literature review method is used identify and interpret microlearning research available in educational settings. The focus is to analyze how microlearning is developed and implemented in educational institutional. The results of this study indicate that the use of the development model does not determine the success of the microlearning product developed and the success of the learning process and improving student achievement is not solely influenced by microlearning, but also influenced by factor outside microlearning. Likewise, the duration of microlearning implementation can be adjusted to the learning objectives to be achieved.